The influence of smoke haze on the incidence of pneumonia in under-five children in Pontianak - Ika Muthya Anggraini; Adi Heru Sutomo; Sukandarrumidi Sukandarrumidi (Berita Kedokteran Masyarakat (BKM), 2016)
Smog effects on pneumonia in under-five children in Pontianak CityPurposeThe purpose of this study was to discover the influence of smoke haze on the incidence of pneumonia in under-five children in Pontianak.MethodsAn ecological study was conducted using time trend analysis, with correlation and multiple linear regression analysis on data of under-five children diagnosed with pneumonia following primary health care diagnosis meeting WHO criteria in Integrated Management of Childhood Illness (MTBS) in Pontianak from January 2010 to January 2014. ResultsThe study found that smoke haze had no direct effects on the incidence of pneumonia in under-five children in Pontianak. Instead, pneumonia in under-five children is influenced by seasons, while smoke haze is also affected by the season, especially during the dry season.ConclusionPneumonia disease in under-five children was influenced by seasons. In the dry season, NO2 content in the air undergoes photochemical reactions that increase O3 levels, while in the rainy season, pneumonia is affected by rainfall and wind velocity that causes air to become moist. The smoke haze generated by forest and land fires in the form of gases and particles has no direct effects on pneumonia in under-five children. Further research to decrease O3 levels in the air, especially in the dry season needs to be done. In addition, policies related to the reduction of hotspots in the dry season also need to be done by the government to minimize the risk factors of pneumonia events.Pneumonia disease in under-five children was influenced by seasons. In the dry season, NO2 content in the air undergoes photochemical reactions that increase O3 levels, while in the rainy season, pneumonia is affected by rainfall and wind velocity that causes air to become moist. The smoke haze generated by forest and land fires in the form of gases and particles has no direct effects on pneumonia in under-five children. Further research to decrease O3 levels in the air, especially in the dry season needs to be done. In addition, policies related to the reduction of hotspots in the dry season also need to be done by the government to minimize the risk factors of pneumonia events.